The Feasibility of Converting Palm Oil Waste into Bioenergy in Sumatra and Kalimantan: A Mini-Review - Loso Judijanto; Hamdani Hamdani; Som Chai (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid expansion of the palm oil industry in Sumatra and Kalimantan has intensified concerns surrounding environmental degradation, waste accumulation, and inefficient resource utilization. Large volumes of solid and liquid waste such as empty fruit bunches, palm kernel shell, fiber, and palm oil mill effluent remain underutilized despite their substantial bioenergy potential. Assuming that all forms of biomass waste can be feasibly converted into energy risks oversimplifying the technical and regulatory complexities involved. Purpose. This mini-review aims to critically assess the feasibility of converting palm oil waste into bioenergy by synthesizing recent scientific findings, technological advancements, and sustainability evaluations from studies conducted between 2015 and 2025. Method. The review employs a qualitative synthesis approach, drawing from peer-reviewed journal articles, government reports, and institutional publications related to waste-to-energy technologies, policy frameworks, and case studies in Indonesia’s palm oil regions. Sources were selected through a systematic screening process using Scopus and ScienceDirect databases. Results. Findings indicate that several technologies such as anaerobic digestion, pyrolysis, gasification, and direct combustion demonstrate promising conversion efficiencies, particularly for palm oil mill effluent and empty fruit bunches. Nonetheless, high capital costs, inconsistent waste collection systems, technological maintenance barriers, and weak policy enforcement continue to hinder large-scale implementation. Socio-economic conditions, especially in rural Kalimantan, further affect the scalability of bioenergy initiatives. Conclusion. The review concludes that converting palm oil waste into bioenergy is technically viable but only conditionally feasible when supported by integrated policy frameworks, community-based waste management, and long-term investment strategies. Strengthening cross-sector collaboration remains essential for sustainable implementation.